Criminal Sanctions Against Money Laundering Crimes in the Perspective of Economic Analysis of Law - Fauzi Yunandi; Arrum Budi Leksono (Yayasan Adra Karima Hubbi, 2023)
Background. Money laundering as a crime in the economic sphere shows that crime is a consequence of economic activity and sustainable development, which is a challenge for the state. Money laundering is the disguise or attempt to disguise the origin of profits from illegal or legitimate activities. Purpose. The purpose of this research is to analyze the money laundering law